2021
DOI: 10.1073/pnas.2102715118
|View full text |Cite
|
Sign up to set email alerts
|

Translational targeting of inflammation and fibrosis in frozen shoulder: Molecular dissection of the T cell/IL-17A axis

Abstract: Frozen shoulder is a common fibroproliferative disease characterized by the insidious onset of pain and restricted range of shoulder movement with a significant socioeconomic impact. The pathophysiological mechanisms responsible for chronic inflammation and matrix remodeling in this prevalent fibrotic disorder remain unclear; however, increasing evidence implicates dysregulated immunobiology. IL-17A is a key cytokine associated with inflammation and tissue remodeling in numerous musculoskeletal diseases, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 62 publications
(106 reference statements)
1
35
1
Order By: Relevance
“…6 However, a growing body of research suggests that inflammation with vascularity and thickening of the rotator interval, capsule, and glenohumeral ligaments are pathologically pivotal to the driving process. 9 , 34 , 35 , 36 Therefore, intervention in these structures is vital to alleviate FS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 However, a growing body of research suggests that inflammation with vascularity and thickening of the rotator interval, capsule, and glenohumeral ligaments are pathologically pivotal to the driving process. 9 , 34 , 35 , 36 Therefore, intervention in these structures is vital to alleviate FS.…”
Section: Discussionmentioning
confidence: 99%
“…6 , 7 The current studies attempt to explain the molecular pathways mechanism of shoulder freezing from the perspective of immunobiology, which is still poorly understood. 8 , 9 The diagnosis of FS is based on recognizing the characteristic features, and radiographs are only valuable for ruling out other pathologies of the shoulder joint. 10 , 11…”
mentioning
confidence: 99%
“…Previous studies have shown that the pathological process of AC begins with an immune response, which then progressively worsens inflammation and eventually leads to fibrosis of the shoulder capsule (16,17). Moeed et al (25)confirmed the role of IL-17A driven AC pathogenesis and revealed the immune landscape of AC from the immune system dominated by macrophages to the immune system rich in T cells. However, the immune mechanisms of AC in the shoulder capsule have not been investigated thoroughly.…”
Section: Introductionmentioning
confidence: 95%
“…While SS was often considered a self-limiting and harmless disease, patients with substantial SS suffer from long-term disabilities, with some patients reporting discomfort 6 years after SS onset, posing a substantial burden to the healthcare system [ 6 ]. The economic impact of SS is underscored by its predilection for adults of working age (8.2% for men and 10.1% for women) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various treatment modalities, including rehabilitation, medication, extracorporeal shockwave therapy, physiotherapy protocols, and surgery, are available; however, the present literature research does not support a definitively effective therapy [ 6 , 9 , 10 ]. The lack of a definitely effective therapy underscores the importance of deepening the understanding of the pathogenesis of SS.…”
Section: Introductionmentioning
confidence: 99%